Using Humor Story to Enhance Students' Speaking Skill - Nisra; Mujahidah (Inspiring: English Education Journal, 2021)
This research was aimed to see the enhancing students’ speaking skill at the tenth grade of SMA Negeri 07 Pinrang. the aim of this research is to get the empirical data of the differences between students’ score of speaking test who were not taught by using humor story and the students who taught by using humor story. The population of this research comprises 271 students is and the sample of the research X IPS as the experimental class comprises 29 students and X MIPA as the control class comprise 33 students. The research method used in this research was quasi-experimental, with a nonequivalent control group design. The data was collected through pretest, posttest, and questionnaire. It aimed to know whether humor story in teaching speaking can enhance students’ confidence in speaking. Based on the calculation, the result of the data analysis by using t-test showed the value of t-test (to) was higher than t-table (tt), to > tt = 3.673 > 1.699, in a significant degree of 0.05 (5%). As the statistical hypotheses show, if t-test (to) > t-table (tt) in a significant degree of 0.05 (5%), it means that the whole brain teaching (Ha) is accepted and the Null Hypothesis (Ho) is rejected. In conclusion, humor story can improve students’ confidence in speaking.